Incisional Hernia of Elective Midline Caesarean Section: Incidence and Risk Factors (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To analyze the incidence and risk factors for development hernia after elective  lower midline caesarean section(ElMCS).Method: A prospective cohort study of 284 women for development of incisional hernia after  repeated elective midline CS. Patients enrollment done from April 13th 2001 and December  12th 2002. follow up to two years for hernia development. Hernias were identified radiographically  or during physical exam. 2-year hernia rates were calculated. Patients were distributed in two  groups, study group consisted of women who had incisional hernia and control group consisted  from women who had not within 2-years postoperatively. Within the two groups potential risk  factors (age, body mass index (BMI), parity, number of previous cesareans, chronic cough,  diabetes mellitus(DM), heart disease, low serum albumin, type of previous incision, anesthesia  type, presence of postoperative fever and wound complications) were collected and statistically  analyzed with the development of incisional hernia (IH).  Setting: Prince Hashem Ben Al-Hussein Hospital, Jordanian Royal Medical Services of Jordan  / Zarqa.  Results: The 2-year hernia was 5.6 % .Independent risk factors of IH development include:  increase in number of previous CSs, wound complications and obesity.  Conclusion: An incisional hernia is higher than previously estimated in women undergoing  ElMCS. Counseling on the family size will reduce the chance for further CS with its associated  risk. Also measures to reduce wound infection after surgery may reduce the incidence of  incisional hernia following ElMCS. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13724 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 9-14